Pelaksanaan Pelatihan Pemetaan Minat Karir dalam Memilih Konsentrasi Perkuliahan Mahasiswa - Fanny kristin Tantyah Sitompul; Isma Shalihi Ahlia; Sheilla Putri Agustin; Iriando Wijaya; Palti Maretto Caesar Manalu; El Shaddai Sandhy Pustap; Musa Kris Payokwa; Rasi Kasim Samosir (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Students’ confusion in selecting a study concentration presents a significant challenge in early career planning. The Management Study Program (S1) at Cenderawasih University faces an imbalance in student interest across concentrations, indicating a limited understanding of individual interests, personality traits, and career prospects. To address this issue, a community service initiative in the form of a career interest mapping workshop was conducted. This training equipped students with interest assessments, personality tests, and skill evaluations. A total of 59 second-semester students participated, facilitated by faculty members from each concentration and HR practitioners. The evaluation results revealed a significant improvement in participants’ understanding of the interrelation between personal interests, personality types, and study concentration choices. The training proved effective in enhancing students’ self-awareness and supporting more informed academic decisions aligned with their potential and personal career goals.